Regional Trade and Investments Integration Results within the South East Europe 2020 Strategy - Efremov, Krum; Majstoroska, Jasmina; Petrovska, Ilijana; Bojadjiev, Marjan (Industrija, 2015)
The aim of this paper is to analyse the level and the dimensions of implementation of trade and investment integration targets in South East Europe (SEE) 2020 Strategy in SEE countries (Albania, Bosnia and Herzegovina, Croatia, Kosovo, Macedonia, Montenegro and Serbia). The main defined targets in SEE 2020 Strategy are to increase the intra-regional trade in goods more than 140% and to increase the overall Foreign Direct Investments (FDI) annual inflow to the region by at least 160%. Regional cooperation is one of the essential factors that should create new relations in SEE, enabling political stability and economic development, as an important preconditions for the countries in their EU accession process. The research methodology for this paper is a comparative analysis of quantitative data and review of the last years’ published official reports and scientific articles. Authors will provide updated situation overview in the countries of SEE with critical analysis of different respective actions and projects needed for achieving the SEE 2020 targets for the Integrated Growth Pillar. This research adds value as a scientific research in the area of trade and investments and provides recommendations for further policy makers’ activities.